Outcomes of Surgery for intramuscular Haemangiomas in the Extremities - Zyluk, Andrzej (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Purpose The objective of this case-series study was an assessment of outcomes of surgery for intramuscular haemangiomas in the extremities.Patients and Methods Three women and one man with a mean age of 28 (23 – 34) years were operated on for intramuscular haemangiomas in the extremities, 3 in the forearms, and 1 in the calf. Three of them, 2 after resection of tumours from the forearm, and one after resection of the tumour in the calf, were available for follow-up assessment at an average of 1.5 (1 – 2) years after surgery. For patients with the tumour in the forearm, preoperative and at the follow-up examination pain was registered with use of the numeric rank scale (NRS), grip strength with the Jamar dynamometer, and function of the extremity with the quickDASH questionnaire. In the patient with the lower limb involvement, pain at the operation site, and efficiency (dexterity) of gait were evaluated.Results All 3 patients with a follow-up examination reported significant reduction of pain. With regard to grip strength and hand function, one patient had significant improvement, whereas in the other, there were no real changes compared to preoperative. The patient with the calf involvement had no symptoms and walked normally. Over the follow-up period, no recurrence was noted.Conclusion The results of this small case-series study show that operative treatment of these rare tumours is safe and effective, however, it may be challenging in some cases.
Keywords: intramuscular haemangioma